Strategi Pelayanan Untuk Meningkatkan Kepuasan Konsumen Ditinjau Dari Etika Bisnis Islam (Pada Toko My Lova Kota Bengkulu) - Septi Handayani; Desi Isnaini; Nonie Afrianty (UNIVED Press, 2023)
The purpose of this study was to determine the service strategy to increase customer satisfaction in terms of Islamic business ethics at the My Lova store, Bengkulu City. This type of research is field research. This study uses a qualitative approach. Data collection techniques were carried out by observation, interviews, and documentation. Then the data is collected, described and analyzed to answer the question. From these results it can be concluded that the My Lova store in Bengkulu City has implemented five service strategies to increase customer satisfaction. The store has also provided timeliness to serve consumers quickly and responsively by using soft words and is ready to help consumers and has also provided a guarantee if there is an error or defect in the goods originating from the store.